High‐mobility pentacene OTFT with TaLaO gate dielectric passivated by fluorine plasma. Issue 10 (28th July 2014) - Han, Chuan Yu; Tang, Wing Man; Leung, Cheung Hoi; Che, Chi Ming; Lai, Pui To
<x xml:space="preserve">Abstract</x> Pentacene thin‐film transistor with high‐κ TaLaO as gate dielectric has been fabricated and shows a carrier mobility of 0.73 cm2/V s, much higher than that based on pure La2O3 (0.43 cm2/V s) due to the smoother surface of the TaLaO film and thus larger pentacene islands grown on it in the initial stage. Moreover, among various times for fluorine‐plasma treatment on the TaLaO gate dielectric, 100 seconds result in the highest carrier mobility of 1.12 cm2/V s due to (1) smoothest oxide surface achieved by fluorine passivation of oxide traps, as measured by AFM and supported by smallest sub‐threshold swing and lowest low‐frequency noise; (2) the largest pentacene grains grown on the smoothest oxide surface, as demonstrated by AFM. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Pentacene islands on on TaLaO or La2O3 gate dielectric with different plasma treatment times. (© 2014 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)